EARLY DETECTION AND INTERVENTIONS TO PREVENT ANEMIA IN PREGNANT WOMEN AT POSYANDU APEL - Triana Indrayani; Jamilah Jamilah; Sulminah Sulminah (Yayasan Education and Social Center, 2023)
The coverage of pregnant women without anemia at Posyandu Apel I and II in 2023 is 60%, while the expected target for pregnant women without anemia is 90%. In the field, it shows that pregnant women with anemia are 40%. One of the solutions to overcome anemia in pregnant women is by carrying out early detection and providing educational interventions. This community service aimed to educate pregnant women about the importance of paying attention to hemoglobin levels during pregnancy. This community service works by collecting data, determining problem priorities, checking HB levels on 15 pregnant women, preparing educational materials, conducting an extension directly to the group of pregnant women with anemia at Posyandu Apel 2, and giving blood-boosting vitamin tablets. An evaluation was carried out by discussion or question and answer. Based on the results, the implementation of this community service extension was attended by 15 pregnant women with anemia and 25 additional participants including lecturers, midwives, and cadres. This activity was carried out together with the team. The participants were very active during the activity with a question-and-answer session